The use of pounds with deaf students in the Math and Science disciplines (Research, Society and Development, 2021)
The present article has as general objective to make an investigation about the origin of the Brazilian sign language (LIBRAS), as well as, a theoretical foundation in analysis of textual productions of contributors of the teaching of LIBRAS. And it has as other objectives: to reflect on the teaching of mathematics and science for deaf students, where the teaching of the subjects is approached showing the teachers' perceptions related to their pedagogical practice; discuss the teacher's way of proceeding when faced with deaf students in a classroom, as well as the importance of understanding the use of LIBRAS to arrive at the student's logical reasoning and with the encouragement of different methodologies. The research exposes the need for educational practice and in the format of how the teacher can adopt new teaching mechanisms, with the aim of significantly promoting the improvement of the linguistic and cognitive structure that will favor the teaching-learning process of the deaf.